Interpersonal discrimination experiences in outpatient care are associated with non-adherence – results of a population survey in Germany - Jens Klein; Anna Christin Makowski; Demet Dingoyan; Olaf von dem Knesebeck (BMC Public Health)
Abstract Background Perceived discrimination is known to be associated with adverse health. However, there is a lack of research on detailed experiences of interpersonal discrimination in health care settings and its relationship with health care outcomes in the general population. The objective was to examine the association between perceived interpersonal discrimination experiences in outpatient care and different issues of non-adherence in a population sample in Germany. Methods Analyses were based on a cross-sectional online survey conducted in Germany. The sample (N = 3,246) was randomly drawn from a panel including the adult population. To assess discrimination, the Discrimination in Medical Settings Scale which originally based on the Everyday Discrimination Scale was used. Five items regrading courtesy, respect, unequal treatment, reserved and dismissive behaviour were introduced to measure the frequency of respective experiences. Patient non-adherence was asked with three questions. Bi- and multivariate analyses adjusted for social characteristics (sex, age, migration history, education, income, health insurance) were conducted. Results Results showed that reporting discrimination experiences was significantly associated with all indicators of non-adherence (not following doctor’s advice, not coming for a follow-up visit, not filling a prescription or obtaining recommended drugs). Moreover, there was a trend indicating the more discrimination experiences reported, the higher the likelihood to be non-adherent. Significant odds ratios in the fully adjusted models vary between 1.77 and 2.58. Conclusions The present study highlights a critical issue regarding health care delivery in Germany and contradicts the goals of health equity. Discrimination reinforces illness behaviour that is known to be detrimental for treatment outcomes. Tackling interpersonal discrimination and stereotype threat in health care should be a major goal in medical education and training. Physician communication skill trainings have been found to positively influence patient adherence which is an important predictor for health outcomes.